Factors associated with parents' willingness to enroll their children in trials for COVID-19 vaccination. Issue 6 (3rd June 2021) - Goldman, Ran D.; Staubli, Georg; Cotanda, Cristina Parra; Brown, Julie C.; Hoeffe, Julia; Seiler, Michelle; Gelernter, Renana; Hall, Jeanine E.; Griffiths, Mark A.; Davis, Adrienne L.; Manzano, Sergio; Mater, Ahmed; et al.
ABSTRACT: The coronavirus disease 2019 (COVID-19) pandemic has taken an unprecedented global toll and vaccination is needed to restore healthy living. Timely inclusion of children in vaccination trials is critical. We surveyed caregivers of children seeking care in 17 Emergency Departments (ED) across 6 countries during the peak of the pandemic to identify factors associated with intent to participate in COVID-19 vaccine trials. Questions about child and parent characteristics, COVID-19 expressed concerns and parental attitudes toward participation in a trial were asked. Of 2768 completed surveys, 18.4% parents stated they would enroll their child in a clinical trial for a COVID-19 vaccine and 14.4% would agree to a randomized placebo-controlled study. Factors associated with willingness to participate were parents agreeing to enroll in a COVID-19 vaccine trial themselves (Odds Ratio (OR) 32.9, 95% Confidence Interval (CI) (21.9–51.2)) having an older child (OR 1.0 (1.0–1.01)), having children who received all vaccinations based on their country schedule (OR 2.67 (1.35–5.71)) and parents with high school education or lower (OR 1.79 (1.18–2.74)). Mothers were less likely to enroll their child in a trial (OR 0.68 (0.47–0.97)). Only one fifth of families surveyed will consider enrolling their child in a vaccine trial. Parental interest in participation, history of vaccinating their child, and the child being older all are associated with parents allowing their child to participate in a COVID vaccine trial. This information may help decision-makers and researchers shape their strategies for trial design and participation engagement in upcoming COVID19 vaccination trials.